Determinants of Islamic Social Reporting in Islamic Banks - Muhson, Nuh Muhammad; Aisyiah, Helti Nur (Journal of Economics and Business Research (JUEBIR), 2024)
The aim of this study is to determine the factors that influence the Islamic Social Reporting (ISR) of Islamic Banks in Indonesia. The factors tested are profitability, company size, leverage, liquidity, and Sharia securities. To identify these factors, the researcher employed a quantitative approach to eleven IB listed with the Financial Services Authority for the period 2019–2022, using the purposive sampling technique in sample selection. The data for these eleven BUS were obtained from annual reports downloaded from the official websites of each Islamic Bank. Subsequently, the obtained data were analyzed using multiple linear regression with the help of the Eviews 12 application, including the steps of a descriptive statistics test, a model selection test, a classical assumption test, and hypothesis testing. Based on the analysis results, only three variables influenced ISR, namely profitability, company size, and liquidity. The direction of the influence was also different. Profitability and liquidity had a negative influence, while company size had a positive influence. Meanwhile, the other two variables, leverage and Sharia securities, did not affect ISR.